Game model based security strategy of heterogeneous controllers in the cloud - Juntai HU; Zhenyu WU; Xiao FU; Yichao WANG (网络与信息安全学报)
Deploying multiple heterogeneous controllers at the control level of a software-defined data center is an effective way to increase security.In view of the deployment strategy of controllers under different security requirements of the network,a game model was presented.Specifically,firstly,the game theory was used to depict the attack and defense game model and solve the Nash equilibrium,and then guided the design of security strategy.Secondly,the impact of the strategy of attack and defense on the security status of the control layer were analyzed.Finally,the simulation results show the effectiveness of the proposed equilibrium strategy,and describe the dynamic interaction strategy.